Readiness of Gen-X English High School Teachers in Integrating Teaching with Technology - Rima Andriani Sari; Made Hery Santosa; Ni Nyoman Padmadewi; Ni Made Ratminingsih; Putu Kerti Nitiasih; I Gede Budasi (Universitas Pendidikan Ganesha, 2023)
During pandemic, almost all school activities rely on the use of technology. Teachers are expected to teach using the online platforms. This study aims at analyzing the readiness of English high school teachers who are categorized into Gen X in integrating technology in teaching, by using TPACK framework. The study applies a descriptive qualitative design. Research subjects were 58 Gen X English high school teachers in one province in Indonesia. Data were collected by distributing online questionnaire to the teachers. Data analysis of triangulation was conducted by doing semi-structured interviews to volunteered teachers. The findings revealed that the Gen X teachers were not ready to integrate teaching with technology. Of all seven integration variables in TPACK, the first level knowledge bases are responded positively. When it comes to the second and third level knowledge bases, the teachers’ responses tend to decrease. Some problems in the technology integration were revealed during the interview. Trainings of teachers’ professionalism for teachers from generation X are considered necessary, especially training on the use of technology and the internet in learning. ICT curriculum integration is also an important issue. Finally, limitations and implications for the education authorities and future research were discussed.